Dynamic Modeling for Prediction of Amino Acid Requirements in Broiler Diets - Guangju Wang; Xin Zhao; Mengjie Xu; Zhenwu Huang; Jinghai Feng; Minhong Zhang (Agriculture)
Accurate prediction of amino acid requirements in fast-growing broilers is crucial for cost-effective diet formulation and reducing nitrogen excretion to mitigate environmental impact. This study developed a dynamic model to predict standardized ileal digestible amino acid requirements throughout broiler growth using a factorial approach and the comparative slaughter technique, considering maintenance, growth, and gender factors. The model was based on an experiment were designed using 480 15-day-old Arbor Acres chickens randomly assigned to 10 groups. A linear equation was derived using established growth and protein deposition curves to calculate maintenance and growth coefficients. Models for five essential amino acids under different amino-acid-to-protein ratios were created (R2 > 0.70). The model effectively estimated daily amino acid needs and specific time intervals. Comparisons with NRC (1994), BTPS (2011), and Arbor Acres manual (2018) showed higher predicted requirements for lysine, methionine, valine, and threonine than Arbor Acres (2018) and BTPS (2011), significantly exceeding NRC (1994). Arginine predictions aligned with BTPS in early stages, but were slightly lower in later stages. This supports the further development of dynamic amino acid models.